2017
DOI: 10.1038/s41598-017-01247-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Membrane Domain Formation Driven by Cholesterol

Abstract: Biological membranes generate specific functions through compartmentalized regions such as cholesterol-enriched membrane nanodomains that host selected proteins. Despite the biological significance of nanodomains, details on their structure remain elusive. They cannot be observed via microscopic experimental techniques due to their small size, yet there is also a lack of atomistic simulation models able to describe spontaneous nanodomain formation in sufficiently simple but biologically relevant complex membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 76 publications
14
99
0
Order By: Relevance
“…binding sites. This is indeed observed in heterogeneous ternary systems 24 (see Section S4.1, ESI †).…”
supporting
confidence: 55%
“…binding sites. This is indeed observed in heterogeneous ternary systems 24 (see Section S4.1, ESI †).…”
supporting
confidence: 55%
“…Molecular dynamic (MD) simulations have revealed structural and kinetic aspects of lipid nanodomains. Recently, all atom MD studies by the groups of Vattulainen and Lyman indicated the presence of substructures within the L o (liquid-ordered) bilayer phase [ 72 , 73 , 74 ]. In such studies, the slow kinetics of phase separation hampers the ability to observe spontaneous segregation into coexisting L o /L d (liquid-disordered) domains.…”
Section: Interactions Of Gpcrs With Their Membrane Environmentmentioning
confidence: 99%
“…Lipid rafts present in cell membranes consist of nanoscale domains that impact on structure and function of the proteins embedded within them [ 126 , 127 ]. Changes in the surrounding lipid composition influences GPCRs, which may be triggered by cholesterol promoting the dynamic assembly of such nanoscale membrane domains [ 74 ]. Cholesterol modulates the physical properties of membranes by increasing the bilayer thickness and order while slowing the dynamics [ 79 ].…”
Section: Interactions Of Gpcrs With Their Membrane Environmentmentioning
confidence: 99%
“…We summarize these observations into three apparent regimes of phase behavior, denoted regime I, miscible The s oc phase observed in this study is similar to a gel phase. While gel phases showing "hexatic" order have recently been reported in terms of the f order parameters, (114,115) the s oc phase is distinct due to the lamellar arrangement of DPPC However, our results demonstrate that these quantities are sensitive to the concentration of Chol in the membrane, and particularly in each domain, which has not been considered in these models.…”
Section: B Three Regimes Of Phase Behaviormentioning
confidence: 49%